Distribution of Cartilage Neoplasm based on Histopathological Types at Dr. Hasan Sadikin General Hospital Bandung Period 2008–2012 - Desy Anggraini; Anglita Yantisetiasti; Darmadji Ismono (Althea Medical Journal, 2015)
Background: Cartilage neoplasms are less common compared to other neoplasms. Its incidence is 22% among all the musculoskeletal neoplasms. Despite many other studies about patient characteristics of theneoplasm in other regions, descriptive data in Bandung city is still unknown. The objective of this study is to determine the distribution of both benign and malignant neoplasms based on their characteristics of histopathological type, gender, age and anatomical site.Methods: The subjects of this descriptive study were taken from the medical records of the patients who had been examined histopathologically in Anatomical Pathology Department at Dr. Hasan Sadikin General Hospital Bandung, Indonesia within the period of 2008 to2012. The sample was obtained using total sampling technique. Patients diagnosed with cartilage neoplasms were included whereas incomplete medical records were excluded. Histopathological type, gender, age and anatomical site of each patients were collected and analyzed.Results: Seventy cartilage neoplasm cases were found. The distribution of cases comprised of 48 (67%) benign and 23 (33%) malignant. The most common benign neoplasm was osteochondroma and chondroma. Benign neoplasms were more prevalent among men and patients <30 years old, while malignant neoplasm was prevalent among women and patients >60 years old. Femur was the most common site for all neoplasms except for chondroma.Conclusions: PThere are differences in characteristic of benign and malignant cartilage neoplasm patients. Both benign and malignant cartilage neoplasms showed differences on the distribution of patient characteristics. [AMJ.2015;2(4):561–7] DOI: 10.15850/amj.v2n4.641